2008
DOI: 10.1007/s00535-007-2125-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of conventional colonoscopy and pan-colonic narrow-band imaging system in the detection of neoplastic colonic polyps: a randomized, controlled trial

Abstract: The pan-colonic NBI system improves the total number of adenomas detected, including significantly more diminutive adenomas, without prolongation of extubation time. These results indicate that routine use of the NBI system for surveillance of diminutive adenomas may be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(70 citation statements)
references
References 27 publications
2
64
1
3
Order By: Relevance
“…Recently, narrow band imaging (NBI) [13] has gained popularity as an alternative to chromoendoscopy. However, three of four trials have not demonstrated an increase in the detection rate of colonic polyps when NBI was compared with conventional colonoscopy [14][15][16][17]. Hence, IC chromocolonoscopy may still be the most reliable method to detect more neoplastic polyps.…”
Section: Introductionmentioning
confidence: 89%
“…Recently, narrow band imaging (NBI) [13] has gained popularity as an alternative to chromoendoscopy. However, three of four trials have not demonstrated an increase in the detection rate of colonic polyps when NBI was compared with conventional colonoscopy [14][15][16][17]. Hence, IC chromocolonoscopy may still be the most reliable method to detect more neoplastic polyps.…”
Section: Introductionmentioning
confidence: 89%
“…Narrow-band imaging. NBI also has been found to increase detection of small and flat adenomas while being easier to perform than pancolonic chromoendoscopy and not prolonging withdrawal time [39]. Interestingly, this technique detects more distal adenomas in a manner that does not correlate with findings in chromoendoscopy trials.…”
Section: Enhanced Endoscopymentioning
confidence: 94%
“…Recently, although several investigators in western countries have been trying to demonstrate its ability to detect colorectal adenomas, most randomized trials have reported negative results (Adler et al, 2008(Adler et al, , 2009). On the other hands, Japanese investigators have reported positive results in their articles (Inoue et al, 2008;Uraoka et al, 2008). Therefore, the efficacy of NBI for detection of colorectal adenoma is still contentious and further investigation is needed.…”
Section: Optical Methods For Minimizing the Overlooking Of Colorectalmentioning
confidence: 99%